2019
DOI: 10.1055/s-0039-1685146
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Posterior Condylar Line and the Transepicondylar Axis: A CT-Based Evaluation

Abstract: Posterior condylar referencing, a common method for determining femoral axial orientation during total knee arthroplasty (TKA), relies upon an assumed consistent relationship between the posterior condylar line (PCL) and the transepicondylar axis (TEA) of 3 degrees rotation. A total of 3,010 computed tomography (CT) scans and three-dimension (3D)-reconstructions for presurgical creation of patient-matched TKA instrumentation were analyzed. Demographic data and five anthropometric measurements (hip–knee angle [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…The sTEA was externally rotated 1.77°to the PCA with a range of 10°which was comparable to the 10°range in the sTEA-PCA angle found by Chalmers et al [25]. Similarly, several studies have found that the sTEA externally rotated to the PCA by about 2-3°on average [26,27]. Restrepo et al also noted that when the posterior cut is made at a fixed 3°external to the posterior condylar axis, there is a significantly greater chance of finding an outlier, which could lead to excessive external or internal rotation of the femoral component, resulting in knee instability and early failure [23].…”
Section: Discussionsupporting
confidence: 79%
“…The sTEA was externally rotated 1.77°to the PCA with a range of 10°which was comparable to the 10°range in the sTEA-PCA angle found by Chalmers et al [25]. Similarly, several studies have found that the sTEA externally rotated to the PCA by about 2-3°on average [26,27]. Restrepo et al also noted that when the posterior cut is made at a fixed 3°external to the posterior condylar axis, there is a significantly greater chance of finding an outlier, which could lead to excessive external or internal rotation of the femoral component, resulting in knee instability and early failure [23].…”
Section: Discussionsupporting
confidence: 79%
“…Despite this, ra-TKA patients present with prolonged surgery time, the blood loss is significantly lower than during mTKA. The surgeon in the present study did not perform more than 15 procedures with NAVIO before enrollment of the patients, where Bell et al evidenced that learning curve was reached at 29 cases with NAVIO [ 37 , 38 ]. The increase in blood loss is not significant in the ra-TKA cohort and these results stands in the line with previously reported outcomes of avoiding of the intramedullary instrumentation [ 21 , 35 , 39 ].…”
Section: Discussionmentioning
confidence: 95%
“…anatomical landmarks intraoperatively [2,4,22,29]. The largest computed tomography(CT) imaging study included approximately 100 patients [31], whereas cadaver studies generally use 20-50 specimens [8].…”
Section: Introductionmentioning
confidence: 99%